SDF-1 chemokine signalling modulates the apoptotic responses to iron deprivation of clathrin-depleted DT40 cells. - Alena Pance; Frank R Morrissey-Wettey; Helen Craig; Alison Downing; Richard Talbot; Antony P Jackson (PLoS ONE)
We have previously deleted both endogenous copies of the clathrin heavy-chain gene in the chicken pre B-cell-line DT40 and replaced them with clathrin under the control of a tetracycline-regulatable promoter (Tet-Off). The originally derived cell-line DKO-S underwent apoptosis when clathrin expression was repressed. We have also described a cell-line DKO-R derived from DKO-S cells that was less sensitive to clathrin-depletion. Here we show that the restriction of transferrin uptake, resulting in iron deprivation, is responsible for the lethal consequence of clathrin-depletion. We further show that the DKO-R cells have up-regulated an anti-apoptotic survival pathway based on the chemokine SDF-1 and its receptor CXCR4. Our work clarifies several puzzling features of clathrin-depleted DT40 cells and reveals an example of how SDF-1/CXCR4 signalling can abrogate pro-apoptotic pathways and increase cell survival. We propose that the phenomenon described here has implications for the therapeutic approach to a variety of cancers.